Are MSCs angiogenic cells? New insights on human nestin-positive bone marrow-derived multipotent cells - Pacini, Simone; Petrini, Iacopo (Frontiers in Cell and Developmental Biology, 2014)
Recent investigations have made considerable progress in the understanding of tissue regeneration driven by mesenchymal stromal cells (MSCs). Data indicate the anatomical location of MSC as residing in the “perivascular” space of blood vessels dispersed across the whole body. This histological localization suggests that MSCs contribute to the formation of new blood vessels in vivo. Indeed, MSCs can release angiogenic factors and protease to facilitate blood vessel formation and in vitro are able to promote/support angiogenesis. However, the direct differentiation of MCSs into endothelial cells is still matter of debate. Most of the conflicting data might arise from the presence of multiple subtypes of cells with heterogeneous morph-functional features within the MSC cultures. According to this scenario, we hypothesize that the presence of the recently described Mesodermal Progenitor Cells (MPCs) within the MSCs cultures is responsible for their variable angiogenic potential. Indeed, MPCs are Nestin-positive CD31-positive cells exhibiting angiogenic potential that differentiate in MSC upon proper stimuli. The ISCT criteria do not account for the presence of MPC within MSC culture generating confusion in the interpretation of MSC angiogenic potential. In conclusion, the discovery of MPC gives new insight in defining MSC ancestors in human bone marrow, and indicates the tunica intima as a further, and previously overlooked, possible additional source of MSC.